Effects of particle size, shape and density on pick-up velocity - Tan, Pei Ting. (2009)
This report aims to investigate how some key parameters such as particle density, size and shape will affect the pickup velocity which is crucial in improving the aerosolization efficiency. In this study, experiments were performed using the same setup, which will be shown later in the report, with 2.05m long of transparent acrylic pipe and inner diameter of 16mm. The available gas flowrate ranges from 10L/min to 50L/min and materials used have particle diameters ranging from 40m to 435m. Two methods namely the weight loss and heap height method were used to measure the pickup velocity. The heap height method determines pickup velocity based on visual observation while the latter uses qualitative analysis. The weight loss method was found to be more sensitive to movement of particles and thus provides a better measurement of pickup velocity. Also, from experiments, a minimum point on the graph of pickup velocity against particle diameter was found similar to literatures. This showed that pickup velocity can be minimized through having the ideal particle diameter. Besides experimenting on the key parameters, particle size distributions were experimented to observe the significance of it on pickup velocity. However, no significant relationship can be found and more needs to be done. From the results of all the experiments performed, it can be concluded that overcoming the dominating interparticle forces of attraction is vital as it determines the magnitude of pickup velocity to a large extend.